2001
DOI: 10.1159/000047270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temporal Cues in Rhesus Monkey Vocal Recognition: Orienting Asymmetries to Reversed Calls

Abstract: An understanding of the acoustic cues that animals use to categorize their vocalizations has important implications for the way we design neuroethological investigations of auditory function. Compared to other species, we know relatively little about the kinds of acoustic features used by nonhuman primates to recognize and categorize vocalizations. To further our understanding, this study explores the role of temporal features in recognition of conspecific vocalizations by rhesus macaques (Macaca mulatta). Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 41 publications
3
49
0
Order By: Relevance
“…Accordingly, language lateralization in humans may reflect a more primitive left-hemispheric dominance for processing basic features of species-typical sounds [16] in which temporal features might be determinant auditory cues for call recognition. This theory is consistent with the results of experiments utilizing time reversed call playbacks in rhesus macaques and dogs resulting in a shift from right-ear to left-ear bias [62,63].…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 88%
“…Accordingly, language lateralization in humans may reflect a more primitive left-hemispheric dominance for processing basic features of species-typical sounds [16] in which temporal features might be determinant auditory cues for call recognition. This theory is consistent with the results of experiments utilizing time reversed call playbacks in rhesus macaques and dogs resulting in a shift from right-ear to left-ear bias [62,63].…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 88%
“…Recently, Gannon et al (2008) demonstrated asymmetry of area Tpt volume in macaque monkeys, with five of six macaque brains displaying a leftward bias. Congruent with these anatomical findings, several studies of non-human primates have revealed a right ear orienting bias when subjects are presented with species-specific vocal calls (Petersen et al 1978;Beecher et al 1979;Hauser & Anderson 1994;Hauser et al 1998;Ghazanfar et al 2001), suggesting left hemisphere specialization for processing communication signals. Similarly, experimental lesion of the left superior temporal cortex in Japanese macaques results in transient disruption of the ability to discriminate conspecific vocalizations, whereas there is no such deficit with right hemisphere lesion (Heffner & Heffner 1984).…”
Section: Discussionmentioning
confidence: 87%
“…These studies have demonstrated that, for example, the interpulse interval in noisy calls as well as the temporal direction of the calls can be relevant for call discrimination Ghazanfar et al, 2001a). Such features are well modeled by the HMMs because the duration of the interpulse interval can be modeled by how long the HMM would remain in a state related to the interpulse interval, and as such, if this interval was shortened, the HMM could detect the call as no longer coming from the appropriate class.…”
Section: Discussionmentioning
confidence: 99%
“…If a feature is not useful for distinguishing among the classes of calls, it would not be a useful feature for the auditory system to encode for the purpose of call discrimination. Behavioral research suggests that primates use multiple features to discriminate among calls, including the interpulse interval in noisy calls, the overall amplitude envelope and the location of inflections in the frequency contour Le Prell and Moody, 2000;Ghazanfar et al, 2001aGhazanfar et al, , 2002. Previous research on the primate auditory cortex suggests that the frequency (Barbour and Wang, 2003) or temporal contrast of sounds is being represented.…”
Section: Introductionmentioning
confidence: 99%